2003
DOI: 10.1063/1.1558658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon on magnetic properties and magnetic entropy change of the LaFe11.5Si1.5 compound

Abstract: Effects of the interstitial carbon atoms on the magnetic properties, especially on the magnetic entropy change, of the LaFe11.5Si1.5 compound, have been studied. X-ray diffraction patterns reveal a monotonous increase of the lattice constant with the concentration of carbon, while the cubic NaZn13-type structure remains unchanged. The Curie temperatures TC of LaFe11.5Si1.5Cy are ∼195, 225, and 241 K for y=0, 0.2, and 0.5, respectively, increasing with the increase of carbon concentration. The maximal magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 17 publications
0
60
0
Order By: Relevance
“…The decrease of |S| for x > 0.4 could be due to impurity phase, which broadens the phase transition. A slightly different carbides LaFe 11.5 Si 1.5 C δ was also studied, [51] and similar effects were observed.…”
Section: Interstitial Effect In La(fe 1-x Si X ) 13mentioning
confidence: 68%
See 2 more Smart Citations
“…The decrease of |S| for x > 0.4 could be due to impurity phase, which broadens the phase transition. A slightly different carbides LaFe 11.5 Si 1.5 C δ was also studied, [51] and similar effects were observed.…”
Section: Interstitial Effect In La(fe 1-x Si X ) 13mentioning
confidence: 68%
“…Our study showed that the entropy change ΔS of Ni 51 The ΔS shows a table-like peak under 5T for Ni 51 Mn 49-x In x . The flat plateau of ΔS should reflect the intrinsic nature of magnetocaloric effect.…”
Section: Magnetic and Magnetocaloric Properties In Mn-based Heusler Amentioning
confidence: 95%
See 1 more Smart Citation
“…[1][2][3] In this case, La-Fe-Si alloy, with NaZn 13 -type La(Fe,Si) 13 phase, has been reported as a promising candidate for magnetic refrigerants. [4,5] La(Fe,Si) 13 alloy exhibits a giant magnetocaloric effect (MCE, which refers to the heating or cooling of magnetic materials due to a varying magnetic field) due to a magnetic field-induced, first-order itinerant electron metamagnetic (IEM) transition above the Curie temperature (T C ). [6] La(Fe,Si) 13 alloy displays a small hysteresis and an isotropic magnetovolume effect accompanied by the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] La(Fe,Si) 13 alloy exhibits a giant magnetocaloric effect (MCE, which refers to the heating or cooling of magnetic materials due to a varying magnetic field) due to a magnetic field-induced, first-order itinerant electron metamagnetic (IEM) transition above the Curie temperature (T C ). [6] La(Fe,Si) 13 alloy displays a small hysteresis and an isotropic magnetovolume effect accompanied by the phase transition. [7][8][9] These properties are beneficial for a cyclic use of La-Fe-Si alloys because of the existing giant magnetocaloric effect.…”
Section: Introductionmentioning
confidence: 99%